Investigation of growth of rhizobium sp. at low concentrations of halogenated compound - Huyop, Fahrul Zaman; Ng, Hong Jing; Yahya, Adibah; Tg. Haziyamin, Tg. Abd. Hamid; Md. Illias, Rosli; Salleh, Abu Bakar (Faculty of Science, 2006)

(untitled)
Halogenated organic compounds are produced industrially in large quantities and represent an important class of environmental pollutants. Bacteria have evolve several strategies for the enzymes to catalysed dehalogenation and degradation of halogenated compounds. The destrution of halogenated chemicals by microorganisms may be influenced by environmental factors or the structure of the chemical itself. One of the reasons suggested for the lack of degradation of organic compounds by microbes is their low concentration. Such organisms appear to be adapted to low substrate concentrations by having high substrate affinity (low Km value) systems. Our current investigation is to study the possibility of growth of Rhizobium sp. at low concentrations of halogenated substrate (2,2-dichloropropionic acid; 2,2DCP). 2,2DCP was chosen because it was widely used as a herbicide (Dalapon). The degradation of low concentrations of 2,2DCP by whole cells of Rhizobium sp. has been achieved (cells doubling time: 12 hours). Rhizobium sp. was able to grow at 0.2 mM 2,2DCP which was 100x lower than the concentration of the substrate routinely used (20 mM) with cells doubling time of 11 hours. Dehalogenase specific activity for crude extracts from cells grown at 20mM and 0.2 mM 2,2DCP PJC minimal media was calculated and the Km values for both enzymes were 0.1mM respevtively. Apparently, no new dehalogenases are required to allow growth on this low concentration of 2,2DCP as judged by dehalogenase properties which is similar to the growth at low substrate concentration. A new isolated bacterium was identified as Methylobacterium sp. by 16S rRNA method was found to be able to degrade 2,2DCP. The bacterium grew in 20mM 2,2DCP PJC minimal medium with a doubling time of 22.80 hours. Degradation of 2,2DCP was detected in growth medium by HPLC technique.